Alcohol and lung cancer risk among never smokers: A pooled analysis from the international lung cancer consortium and the SYNERGY study. Issue 9 (27th February 2017) - Fehringer, Gordon; Brenner, Darren R.; Zhang, Zuo‐Feng; Lee, Yuan‐Chin Amy; Matsuo, Keitaro; Ito, Hidemi; Lan, Qing; Vineis, Paolo; Johansson, Mattias; Overvad, Kim; Riboli, Elio; Trichopoulou, Antonia; et al.
Abstract : It is not clear whether alcohol consumption is associated with lung cancer risk. The relationship is likely confounded by smoking, complicating the interpretation of previous studies. We examined the association of alcohol consumption and lung cancer risk in a large pooled international sample, minimizing potential confounding of tobacco consumption by restricting analyses to never smokers. Our study included 22 case‐control and cohort studies with a total of 2548 never‐smoking lung cancer patients and 9362 never‐smoking controls from North America, Europe and Asia within the International Lung Cancer Consortium (ILCCO) and SYNERGY Consortium. Alcohol consumption was categorized into amounts consumed (grams per day) and also modelled as a continuous variable using restricted cubic splines for potential non‐linearity. Analyses by histologic sub‐type were included. Associations by type of alcohol consumed (wine, beer and liquor) were also investigated. Alcohol consumption was inversely associated with lung cancer risk with evidence most strongly supporting lower risk for light and moderate drinkers relative to non‐drinkers (>0–4.9 g per day: OR = 0.80, 95% CI = 0.70–0.90; 5–9.9 g per day: OR = 0.82, 95% CI = 0.69–0.99; 10–19.9 g per day: OR = 0.79, 95% CI = 0.65–0.96). Inverse associations were found for consumption of wine and liquor, but not beer. The results indicate that alcohol consumption is inversely associated with lung cancer risk, particularly among subjects with low to moderate consumption levels, and among wine and liquor drinkers, but not beer drinkers. Although our results should have no relevant bias from the confounding effect of smoking we cannot preclude that confounding by other factors contributed to the observed associations. Confounding in relation to the non‐drinker reference category may be of particular importance. Abstract : What's new? When considering how alcohol affects lung cancer risk, it's been challenging to tease out the impact of alcohol from that of smoking. Now, these authors have pooled data from 22 international studies involving only people who have never smoked. They've conducted the largest case‐control analysis to date looking at alcohol and lung cancer risk in the absence of tobacco. People who drank low to moderate amounts of wine and liquor particularly – not beer – did have a lower risk of lung cancer, although confounding by factors other than smoking, particularly in relation to the non‐drinkers reference group, cannot be ruled out.